Depression and associated factors among patients with type 2 diabetic mellitus in Ethiopia: a cross sectional study - Dukato, Amanuel; Beyamo, Abera; Habte Hailegebireal, Aklilu; Teklehaimanot, Wegayehu Zeneb; Ayfokru, Abatwoy; Alemnew, Metages; Birhanu Abate, Daniel; Abemie, Worku; Mengistu, Bethlehem Taye; Ayehu Dessie, Yihenew; Mengstie, Leweyehu Alemaw; Girma, Bekahegn (Frontiers in Psychiatry, 2024)
Background: Depression is a significant public health concern in both developed and developing countries. The burden of depression is particularly high among patients with chronic illnesses in developing countries, creating a dual challenge for both patients and the community.However, depression goes undiagnosed in 50%-75% of patients with chronic conditions such as diabetes mellitus. Additionally, there is limited information about the prevalence of depression among diabetic patients in Ethiopia. Therefore, this study aimed to assess the prevalence and associated factors of depression among type 2 diabetic patients in Ethiopia.Method: An institution-based cross-sectional study was conducted on 376 randomly selected type 2 diabetic patients. Data were collected through face-to-face interviews and from patients' follow-up records. The data were entered into EpiData version 4.6 and analysed using STATA 14. Bivariable and multivariate logistic regression analyses were employed to identify associated factors. Variables with a p-value of less than 0.25 in the bivariable analysis were selected for multivariate logistic regression. Model fitness was assessed using Hosmer-Lemeshow's test, and associations were reported using adjusted odds ratios with 95% confidence intervals Results: In this study, the prevalence of depression among type 2 diabetic patients was found to be 69.72% (95% CI: 64.75, 74.27). Three factors were significantly associated with depression in these patients: the duration of diabetes mellitus since diagnosis [AOR: 1.17; 95% CI (1.02, 1.34)], glycaemic control [AOR: 1.8; 95% CI (1.09, 3.01)] and cigarette smoking [AOR: 2.18; 95% CI (1.07, 4.46)].The prevalence of depression among type 2 diabetic patients was high. The Federal Ministry of Health, stakeholders, and the Ethiopian Diabetes Association should collaborate to reduce this burden. Mental health assessment and treatment should be integrated into chronic care follow-up services. Additionally, healthcare providers should closely monitor and counsel patients who smoke and those with poor glycemic control.